Dry Chemistry of Ferrate(VI): A Solvent‐Free Mechanochemical Way for Versatile Green Oxidation. Issue 34 (20th July 2018) - Zhang, Zhao‐Yang; Ji, Deyang; Mao, Wenting; Cui, Yu; Wang, Qing; Han, Lu; Zhong, Hongliang; Wei, Zhongming; Zhao, Yixin; Nørgaard, Kasper; Li, Tao
Abstract: The +6 oxidation state of iron generally exists in the form of ferrate(VI) with high redox potential and environmentally friendly nature. Although ferrate(VI) has been known for over a century, its chemistry is still limited to the solvent‐based reactions that suffers from the insolubility/instability of this oxidant and the environmental issues caused by hazardous solvents. Herein, we explore the solvent‐free reactivity of ferrate(VI) under mechanical milling, revealing that its strong oxidizing power is accessible in the "dry" solid state towards a broad variety of substrates, for example, aromatic alcohols/aldehydes and carbon nanotubes. More significantly, solvent‐free mechanochemistry also reshapes the oxidizing ability of ferrate(VI) due to the underlying solvent‐free effect and the promotive mechanical actions. This study opens up a new chemistry of ferrate(VI) with promising application in green oxidative transformation of both organic and inorganic substrates. Abstract : A high oxidation state : Ferrate(VI) compounds under solvent‐free conditions display intrinsically strong and unexpected oxidizing power. The power can be readily harnessed and promoted by mechanochemistry for green oxidative transformations of both organic and inorganic substrates.